Population dynamics of Escualosa thoracata (Valenciennes, 1847) in Matang Mangrove Estuaries, Perak, Malaysia - Mohd Khatib, Mohd Azim; Sarker, S. M. Nurul Amin Harmuj Ali; Arshad, Aziz; Md. Yusoff, Fatimah (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
An investigation on population dynamic parameters like growth, natural mortality, fishing mortality and recruitment pattern of clupeid fish, Escualosa thoracata (Valenciennes, 1847) in Matang Mangrove Estuaries, Perak, Malaysia was conducted from September 2015 to August 2016. Monthly length frequency data of E. thoracata were analyzed by FiSAT software to evaluate the mortality rates and its exploitation level. The relationship between total length and body weight was estimated as W= 0.0009TL2.9957 (R2 = 0.8954). Asymptotic length (L) and growth co-efficient (K) was estimated at 10.86 cm and 1.70 yr-1, respectively. Total mortality (Z), natural mortality (M) and fishing mortality (F) was calculated at 5.84 yr-1, 3.47 yr-1 and 2.38 yr-1, respectively. Exploitation level (E) of E. thoracata was found to be 0.41. The fishing pressure was 18% below the optimum level of exploitation (E = 0.50). It is revealed that the stock of E. thoracata might be under-exploited in Matang Mangrove Estuaries.